2018
DOI: 10.1096/fj.201800948rr
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor recruitment and adipogenic lipolysis contribute to the anabolic actions of parathyroid hormone on the skeleton

Abstract: Intermittent administration of parathyroid hormone (PTH) stimulates bone formation in vivo and also suppresses the volume of bone marrow adipose tissue (BMAT). In contrast, a calorie‐restricted (CR) diet causes bone loss and induces BMAT in both mice and humans. We used the CR model to test whether PTH would reduce BMAT in mice by both altering cell fate and inducing lipolysis of marrow adipocytes. Eight‐week‐old mice were placed on a control (Ctrl) diet or CR diet. At 12 wk, CR and Ctrl mice were injected dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 46 publications
(50 reference statements)
6
48
0
Order By: Relevance
“…This hormone induces lipolysis in adipocytes 169 and has been shown to reduce bone marrow adiposity when administered to mice 170,171 . In vitro work using an elegant co-culture system containing adipocytes and osteoblast progenitors demonstrated that after lipolysis, fatty acids are transferred from adipocytes to cells of the osteoblast lineage 171 . Although additional studies will be necessary, the transferred fatty acids could be speculated to be metabolized as an energy source.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…This hormone induces lipolysis in adipocytes 169 and has been shown to reduce bone marrow adiposity when administered to mice 170,171 . In vitro work using an elegant co-culture system containing adipocytes and osteoblast progenitors demonstrated that after lipolysis, fatty acids are transferred from adipocytes to cells of the osteoblast lineage 171 . Although additional studies will be necessary, the transferred fatty acids could be speculated to be metabolized as an energy source.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Teriparatide treatment in osteopenic women reduces BMAT (229) and animal studies showed that this effect can be recapitulated by genetic deletion of the parathyroid hormone receptor in skeletal stromal cells (56). Interestingly, additional studies from the Rosen lab showed that the effect of PTH is not only on the differentiation of the SSC into the adipocytic lineage, but that Parathyroid Hormone (PTH) can also induce lipolysis in BM adipocytes (230). In addition, growth hormone (GH) is an important regulator of skeletal growth and growth hormone deficiency or resistance has been associated with changes in BMAT.…”
Section: Endocrine Regulationmentioning
confidence: 99%
“…While additional studies will be necessary, this paradigm is congruent with findings from Maridas et. al (105) that tracked the transfer of fatty acids from adipocytes to bone marrow stromal cells as well as the established ability of PTH to induce lipolysis in adipocytes (106). Likewise, the reduction in marrow adipose tissue volume after intermittent PTH treatment suggests that marrow adipocytes represent an energy reserve that provides fatty acids to fuel the anabolic activity of osteoblasts (105,107).…”
Section: Parathyroid Hormone Signalingmentioning
confidence: 99%
“…al (105) that tracked the transfer of fatty acids from adipocytes to bone marrow stromal cells as well as the established ability of PTH to induce lipolysis in adipocytes (106). Likewise, the reduction in marrow adipose tissue volume after intermittent PTH treatment suggests that marrow adipocytes represent an energy reserve that provides fatty acids to fuel the anabolic activity of osteoblasts (105,107). The finding that PTH can increase bone mass even under conditions of caloric restriction suggests that the relationship between PTH activity and metabolism is more complex and worthy of further study (105).…”
Section: Parathyroid Hormone Signalingmentioning
confidence: 99%